Hantavirus-Specific CD8(+)-T-Cell Responses in Newborn Mice Persistently Infected with Hantaan Virus - Araki, Koichi (American Society for Microbiology, 2003)
The relationship between virus-specific CD8(+)-T-cell responses and viral persistence was studied in mice by using Hantaan virus (HTNV). We first established a simple method for measuring levels of virus-specific CD8(+) T cells by flow cytometry. Next, to produce a mouse model of persistent HTNV infection, newborn mice were inoculated subcutaneously within 24 h of birth with 1 or 0.1 50% newborn mouse lethal dose of HTNV. All mice that escaped lethal infection were persistently infected with HTNV until at least 30 days after virus inoculation and had no virus-specific CD8(+) T cells producing gamma interferon (IFN-γ). Subsequently, the virus was eliminated from some of the mice, depending on the appearance of functional virus-specific CD8(+) T cells, which have the ability to produce IFN-γ and tumor necrosis factor alpha (TNF-α) and have cytotoxic activity. Neutralizing antibodies were detected in all mice, regardless of the presence or absence of virus. In the acute phase, which occurs within 30 days of infection, IFN-γ-producing HTNV-specific CD8(+) T cells were detected on day 15 after virus inoculation. However, TNF-α production and the cytotoxic activity of these specific CD8(+) T cells were impaired and HTNV was not removed. Almost all of these specific CD8(+) T cells disappeared by day 18. These results suggest that functional HTNV-specific CD8(+) T cells are important for clearance of HTNV.